Wall Street - Stone, Oliver; Pressman, Edward R.; Weiser, Stanley; Douglas, Michael, 1944-; Sheen, Charlie; Hannah, Daryl; Sheen, Martin; Twentieth Century-Fox Film Corporation (Beverly Hills : 20th Century Fox Home Entertainment, 2001)
A young and impatient stockbroker is willing to do anything to get to the top, including trading on illegal inside information taken through a ruthless and greedy corporate raider who takes the youth under his wing.
Special features: Trailer -- Documentary -- Audio commentary by director Oliver Stone -- Interactive menu.
Originally released as a motion picture in 1987.
Music by Stewart Copeland ; director of photography, Robert Richardson.
Michael Douglas, Charlie Sheen, Daryl Hannah, Martin Sheen.
DVD, region 2; widescreen (16:9); aspect ratio 1.85:1; Dolby digital 5.1 (English), Dolby surround (Spanish).
In English dubbed Spanish dialogue with optional English and Spanish subtitles.
Keywords: New York Stock Exchange -- Drama; Investment bankers -- New York (State) -- New York -- Drama; Stockbrokers -- New York (State) -- New York -- Drama; Wall Street (New York, N.Y.) -- Drama; Thrillers (Motion pictures); Feature films; Fiction films